Myths and Facts About Heart Failure with Preserved Ejection Fraction: Risk Factors, Longevity, Potential Pharmacological and Exercise Interventions - Chung-Lieh Hung; Charles Jia-Yin Hou; Gwo-Chi Hu; Jen-Yuan Kuo; Chia-Yu Hsu; Cheng-Ho Tsai; Hung-I Yeh; Bernard E. Bulwer; Ya-Ching Hsieh (International Journal of Gerontology, 2013)
Significant progress in our understanding of risk factors and interventions in heart failure, a leading cause of death and disability, has occurred in recent years. Several advances in therapy for heart failure with reduced left ventricular systolic function (i.e., systolic heart failure) have led to significantly improved outcomes. Treatment options for diastolic heart failure, also known as heart failure with preserved ejection fraction (HFpEF), by contrast, remain comparatively limited. In part, this is due to gaps in our understanding of the underlying pathophysiology and the lack of standardized criteria for its diagnosis and classification. Aging and hypertension remain the leading causes of HFpEF; increased ventricular and vascular stiffness is a feature of both. Comorbidities such as diabetes, renal insufficiency, and metabolic abnormalities further aggravate disease process, and data regarding effective treatment are lacking. This article discusses the risks, mechanisms, and outcomes of HFpEF from previous studies, and summarizes potential interventions that may provide new insights into our understanding of the disease and its treatment.